Engineering Gyroid‐Structured Functional Materials via Templates Discovered in Nature and in the Lab. Issue 38 (20th August 2015) - Wu, Liping; Zhang, Wang; Zhang, Di
<x xml:space="preserve">Abstract</x> In search of optimal structures for functional materials fabrication, the gyroid (G) structure has emerged as a promising subject of widespread research due to its distinct symmetry, 3D interconnected networks, and inherent chiral helices. In the past two decades, researchers have made great progress fabricating G‐structured functional materials (GSFMs) based on G templates discovered both in nature and in the lab. The GSFMs demonstrate extraordinary resonance when interacting with light and matter. The superior properties of GSFMs can be divided into two categories based on the dominant structural properties, namely, dramatic optical performances dominated by short‐range symmetry and well‐defined texture, and effective matter transport due to long‐range 3D interconnections and high integrity. In this review, G templates suitable for fabrication of GSFMs are summarized and classified. State‐of‐the‐art optical applications of GSFMs, including photonic bandgap materials, chiral devices, plasmonic materials, and matamaterials, are systematically discussed. Applications of GSFMs involved in effective electron transport and mass transport, including electronic devices, ultrafiltration, and catalysis, are highlighted. Existing challenges that may hinder the final application of GSFMS together with possible solutions are also presented.